Effect of multiple deconvolution parameters on the resolvability of decay rates of multiexponential signals - Jibia, Abdussamad U.; Salami, Momoh Jimoh Emiyoka; Khalifa, Othman Omran (2008)
Noise reduction in deconvolution process has been a challenge to researchers in the field of signal processing. The problem is ill-posed and various algorithms have been developed to reduce noise enhancement. The effect of using multiple noise-compensating parameters in the deconvolution of multiexponential signals is considered in this paper. Three parameters are simultaneously adjusted to obtain optimal reduction in noise. It is shown that this approach performs better than a single parameter approach.